Children aged two to four are able to scribble and draw using a smartphone app. (9th April 2017) - Yadav, Savita; Chakraborty, Pinaki
Abstract: Aim: Drawing apps are an attractive medium, and this study assessed the fluency and skills with which children aged two to four drew using an app on a smartphone. Methods: We provided 90 children between two and four years of age with a drawing app at a playschool in an upper‐class suburb in New Delhi in November 2016. The app allowed them to draw by sliding their finger on the screen and selecting the drawing colour from a palette. The children were given five minutes to draw with the app. Results: All the children were able to draw with the app. The children aged two and three were in the scribbling stage. The children aged two typically drew zigzag lines with a single colour, while the children aged three were able to draw distinct lines and shapes with multiple colours. The children aged four had moved from the scribbling stage to the preschematic stage. They drew multicoloured figures identifiable as real‐world objects and were able to explain what they were drawing. Conclusion: We found that drawing apps were appropriate for young children aged two to four and may be used by them along with other drawing media.